0250 The Day-to-Day Associations Between Sleep Characteristics, Affect, and Affect Reactivity. (27th May 2020) - Wong, P M; Hasler, B P; Kamarck, T; Wright, A; Hall, M; Carskadon, M A; Manuck, S B
Abstract: Introduction: Despite the high co-occurrence of sleep and mood disturbances, day-to-day associations between sleep characteristics (sleep duration, continuity, timing) and dimensions of mood (positive affect, PA, and negative affect, NA) remain unclear. Few field studies have tested whether sleep changes may affect mood by altering people's emotional response to daily experiences outside the laboratory. The current study aimed to examine how sleep characteristics influence affective states and a measure of emotional response to daily experiences—affect reactivity. Methods: Participants were healthy, midlife adults (30–54 yrs old, N =462, 47% male) drawn from the Adult Health and Behavior Project- Phase 2 study. Sleep was measured with actigraphy across a 4-day monitoring period; hourly self-report measures of affect, work demand, and social interactions were collected via ecological momentary assessment. Affect reactivity was quantified as hour-to-hour changes in affect following these daily experiences. We used hierarchical linear modeling to examine whether sleep characteristics on a given night predicted average daily affect and moderated affect reactivity the following day. Results: When participants slept later than their average sleep time on a given night, they reported greater NA the following morning (before 12pm) and afternoon (12-6pm; B's =.03, p's<.05). When participants slept longer than their average sleep duration, they subsequently reported greater NA throughout the following day (B's =.02, p's<.05). Sleep efficiency was unrelated to affect report ( p 's >.05). While episodes of greater work demand and social conflict predicted lower PA and higher NA (p's<.05), participants' sleep characteristics did not moderate these associations (p's>.05). Conclusion: Overall, our findings suggest proximal associations between sleep characteristics and next-day mood. While previous studies have shown effects of sleep disruptions on affect reactivity, we did not observe such associations in the context of small, day-to-day fluctuations in sleep characteristics among healthy individuals. Support: National Institutes of Health Grant PO1 HL040962 (to S.B.M.).